Processos de ensino-aprendizagem em artes visuais no instituto de cegos do Recife - Monteiro, Dayane Danubia (2021)
This study is based on the interest in understanding the teaching-learning processes of teachers of Arts at IAPQ. The Institute works in specialized care for people with Visual Impairment, providing educational training; professionalizing, cultural and leisure activities. The methodology used was qualitative research, and as theoretical foundation the authors Smith (2008), Wernek (1997), Cianciosa (2014) and Mantoan (2003) in Special Education and Inclusive Education, Mazzota (2003) and Lewin (1941) to talk about the historical context of the IAPQ and Non-Formal Education, Marconi and Lakatos (2013) and Michel (2009) to discuss the teaching-learning practices in the IAPQ. The data of this investigation were collected from bibliographical research, in the private collection of the IAPQ, in the Public Archive of Recife, and through the realization of 6 (six) interviews carried out by personal and technological means. The research shows that there was a variety of short-term Arts courses/activities offered by the Institute, resulting from voluntary and sporadic work by employees of Santa Casa de Misericórdia or even from temporary partnerships signed between the Institute and other institutions. Mostly, they focused on manual activities and with the specific purpose of producing income. The testimonies made clear the understanding that these activities did not go beyond doing, that there were no broader reflections that could contribute to sociocultural expansion of each one or even the attribution of meanings and meanings to what was done. Ideally, special education should take place at the beginning, because the individual needs specific education such as braille and the use of a cane. The student also needs to be inserted in inclusive education, experiencing exchanges with other people and the Arts teacher, in their training trajectory, needs to go through these spaces to understand these adaptation processes, and work with these students in regular education more equality. Keywords: